ROLE OF TRUST IN GHOST KITCHENS: WHAT DRIVES IT AND WHY IT MATTERS - Laurence; Sinta (Faculty of Economics and Business Universitas Pelita Harapan, 2025)
Indonesia is a country rich in cultural diversity, including in the food and beverage sector. In 2020, the food and beverage industry experienced its slowest growth due to the impact of the Covid-19 pandemic. This global crisis significantly altered consumer behavior, particularly in how individuals procure food and beverages from restaurants. One notable outcome of this shift is the emergence and growing popularity of ghost kitchens. This study investigates the relationships among several key variables: food quality, price, online reviews, trust, purchase intention, and word of mouth. The primary objective is to examine and analyze the positive influences among these variables. The research employs a quantitative approach through the distribution of questionnaires to Indonesian consumers aged 17 to 42 years—categorized as Generation Z and millennials—who have made purchases from ghost kitchens within the past three months. Data were collected using purposive sampling, resulting in 436 valid responses. The data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach, implemented through SmartPLS. The theoretical framework is grounded in consumption value theory, the theory of planned behavior, and prospect theory. The findings indicate that food quality, price, and online reviews significantly and positively influence consumer trust. Furthermore, trust has a significant and positive effect on both purchase intention and word of mouth.